Book Review / Рецензия книг / Buchbesprechung - Meier, Markus; Óhidy, Andrea (International Dialogues on Education Journal, 2016)
Oerter, Rolf (2014): Der Mensch, das wundersame Wesen. Was Evolution, Kultur und Ontogenese aus uns machen Tamás Kozma et. al. (2015): Learning Regions in Hungary: From Theory to Realities. Debrecen: Center for Higher Education Research and Development Hungary